Seroprevalence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) among healthcare providers prior to the vaccine era in an integrated midwestern healthcare system - Elie A. Saade; Xiaochun Zhang; Jaime H Noguez; Lisa M. Stempak; Daniel Tisch; Christine Schmotzer; Robert A. Salata (Cambridge University Press, 2022)
We performed severe acute respiratory coronavirus virus 2 (SARS-CoV-2) antinucleocapsid IgG testing on 5,557 healthcare providers and found a seroprevalence of 3.9%. African Americans were more likely to test positive than Whites, and HCWs with household exposure and those working on COVID-19 cohorting units were more likely to test positive than their peers.